A song turned sideways would sound as sweet. (5th May 2021) - Ferguson, Zachary
Abstract: Markosian (2020) presents an argument against certain theories of time based on the aesthetic value of music. He argues that turning a piece of music sideways in time destroys its intrinsic value, which would not be possible if the Spacetime Thesis were true. In this paper I show that sideways music poses no problems for any theory of time by demonstrating that turning a piece of music sideways does not affect its intrinsic value. I do this by appealing to spatial analogies that highlight the similarities between spatial and temporal rotations.